Pengaruh Variasi Latihan Terhadap Keterampilan Gerak Dasar Tendangan Dollyo Chagi - Selis, Selis; Rahayu, Ega Trisna; Nugroho, Setio (Universitas Hamzanwadi, 2024)
This study aims to evaluate the effect of training variations on the basic movement skills of dollyo chagi kicks in taekwondo extracurricular at SMAN 1 Karawang. This study adopted a descriptive quantitative approach. In the research design, an exploratory sequential design model was used using an experimental approach with a pretest and posttest control group design. The study population consisted of 31 students involved in taekwondo extracurricular activities, which were taken using proposive sampling technique. Data collection techniques using tests and statistical analysis. The Shapiro Wilk data normality test is said to be normally distributed data if the significance value is more than 0.05 or Sig > 0.05. obtained Sig (2tailed) value of 0.000, significance value (2 tailed) 0.000 < 0.05. The N Gain percent value that is smaller or less than 40% is interpreted into the ineffective category. The N Gain percent value is between 40% 55% interpreted in the less effective category. This indicates an increase in learning completeness before and after learning to write discussion text understanding and basic movement skills of dollyo chagi kick.